COMPARATIVE ANALYSIS OF SPECIAL WORDS: SIMILAR AND DIFFERENTIAL ASPECTS (American Journal of Pedagogical and Educational Research, 2025)
In the history of world linguistics, the study of exclamatory, imitative and modal words has its own historical stages. In all periods, much attention was paid to their semantics, contextual meaning, etymology, language typology, methodological functions, their place in the text. Exclamatory and imitative words are sometimes confused systematically and structurally due to the fact that they arise as a result of the impact of sounds and images in nature. But these are separate categories, and the main difference lies in their semantic nature, grammatical basis and independent syntactic function in a sentence. In the article, we analyze the linguistic and speech progress of exclamation words in the Uzbek language using examples from the work of Mahmoud Kashgari “Devonul lugotut turk”.